Persepsi Guru terhadap Tantangan Pembelajaran Bagi Siswa Tunarungu di SLB PGRI Kamal - Endang Sulistianingsih; Nova Estu Harsiwi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to explore teachers' perceptions of challenges in the learning process for deaf students at SLB PGRI Kamal, Bangkalan. With a descriptive qualitative approach, data is collected through interviews, observations, and documentation. The results of the study show that teachers face challenges in the form of students' difficulties in understanding instruction, limited communication, and lack of pedagogical competence of teachers in special education. In response, teachers apply adaptive strategies such as the use of sign language, visual media, simplification of materials, and an individualized approach. The support of the school environment, such as conducive learning spaces and cooperation between teachers, also strengthens the effectiveness of learning. Teachers consider learning to be quite effective, especially for students who get emotional support and visual learning. This study recommends continuous training for teachers and strengthening cooperation between schools and parents to improve the quality of education for deaf students.